Proses Pengadaan Sumber Daya Manusia Perangkat Desa di Kabupaten Sidoarjo - Rodiyah, Isnaini (PERSPEKTIF, 2024)
The implementation of village government cannot be separated from the role of village officials in realizing public services and good governance. Recruitment and selection of village officials need to be carried out strictly to obtain quality human resources. This study aims to describe the recruitment and selection patterns of village officials in Sidoarjo Regency. The research method used is descriptive with a qualitative approach. Data were collected through interviews, observation and documentation. Data analysis used the Miles and Huberman interactive model including data collection, reduction, and presentation, as well as conclusion drawing. The results showed that the pattern of recruitment and selection of village officials included the stages of announcement, administrative selection, examination, announcement of examination results, and inauguration. The online exam was preceded by a server trial before implementation. The exam consisted of three types of questions, namely general knowledge, nationality, and government, including 100 questions. The results of the exam are announced in the form of scores and rankings of participants as well as the position chosen.  Participants who pass the exam are then officially inaugurated as village officials.